Some questions of methodology for conducting tests of radiation protection of armored objects - Dovbnya, A.N.; Starenky, V.P.; Goncharov, I.G.; Cherniavskіy, I.Y.; Anashkin, O.A.; Vlasenko, V.O.; Ovcharenko, K.S. (Вопросы атомной науки и техники, 2020)
The results of approbation of the methodology for laboratory testing a materials for armored objects radiation protection by determining their half-value layer for nuclear radiations, which are typical for the main situations of the radiation factor effect in modern conditions, are presented. Представлені результати апробації методології лабораторних випробувань матеріалів протирадіаційного захисту бронеоб’єкту шляхом визначення їх шару половинного ослаблення до ядерних випромінювань, які характерні для основних ситуацій впливу радіаційного фактора у сучасних умовах. Представлены результаты апробации методологии лабораторных испытаний материалов противорадиационной защиты бронеобъектов путем определения их слоя половинного ослабления к ядерным излучениям, которые характерны для основных ситуаций воздействия радиационного фактора в современных условиях.